An Aramaic Joint Venture Agreement: A New Interpretation of the Bauer-Meissner Papyrus - Szubin, H. Z. (Bulletin of ASOR, 1992)
A new collation and legal study of the oldest Aramaic papyrus contract disclose an instrument of agreement akin to the modern joint venture. On June 3, 515 B. C. E., Padi, son of Daganmelech, possibly a Philistine, contracted with an Egyptian farmer, Aḥa son of Apion, regarding Padi's royal allotment in Krb, probably Korobis in Middle Egypt. The terminology points to a sophisticated legal arrangement that goes beyond the standard tenant-farmer lease agreement. As coventurors in a joint enterprise, the parties share equally (šwywy) both profits and losses (ṭbʾ wlḥyʾ nplg). Each party seeks to limit his exposure to risks and liabilities and to guarantee the contracted performance, e. g., by means of a limited defension clause and forfeitable bond. Stimulated by a new analysis of Talmudic sources, the Aramaic document and Akkadian, demotic, and Greek contracts are reinterpreted and reclassified.